Atividade antinociceptiva, anti-inflamatória e antioxidante do extrato etanólico bruto e fração alcalóide da Waltheria viscosissima A. St. Hil - Malvaceae - Viegas, Claudenise Caldas da Silva Dantas (2022)
The Waltheria viscosissima A. St.- Hil (Malvaceae) is also known as ‘Malva branca’, has been reported ethnopharmacologically to have antinociceptive and anti- inflammatory properties. The objective of this study is to lucidate the antinociceptive, anti-inflammatory and antioxidant activity of the crude ethanol extract (EEBWa.v) and alkaloid fraction (FAWa.v) of aerial parts of the W. viscosissima in Swiss mice. Initially, the acute toxicity test of the EEBWa.v and FAWa.v was performed at a dose of 2000 mg/kg, intraperitoneally (i.p.), and the behavioral screening through the Rota rod test with EEBWa.v and FAWa.v (50, 100 e 200 mg/kg), Diazepam (4 mg/kg). EEBWa.v and FAWa.v (50, 100 and 200 mg/kg) and morphine (10 mg /kg) were used in vivo tests of chemical nociception induced by acetic acid (0.6%; 10 mg/kg) and formalin (2.5%) in Swiss male mice. Acute inflammation was assessed by the prostaglandin induced paw edema model and induced peritonitis by carrageenan (1%), in vivo tests, whose groups were the control (inflammation induced without treatment) and the groups treated with EEBWa.v (100 mg/kg), FAWa.v (100 mg/kg) and indomethacin (10 mg/kg) or dexamethasone (2 mg/kg). After the carrageenan induced peritonitis procedure, the animals were euthanized and the peritoneal fluid was collected to evaluate cell migration and redox balance (malondialdehyde - MDA and Total Antioxidant Capacity - TAC). The mechanism of action was evaluated by the formalin test with caffeine (10 mg/kg, i.p.), naloxone (5 mg/kg, i.p.) and glibenclamide (10 mg/kg, i.p.). The morphine, EEBWa.v (50 and 100 mg/kg) and FAWa.v (100 mg/kg) significantly reduced the number of abdominal contortions when compared to the control group and FAWa.v (100 mg/kg) was superior to FAWa.v (200 mg/kg). In the formalin-induced nociception model, in the neurogenic phase EEBWa.v (50 and 200 mg/kg) significantly reduced the number of paw licks. In the inflammatory phase FAWa.v (100 mg/kg) was superior to EEBWa.v (200 mg/kg). EEBWa.v and FAWa.v (100 mg/kg) proved to be significant for the next experiments. Both samples showed reduction in paw edema and cell migration, as well as those treated with indomethacin and dexamethasone, in animals with inflammation induced by prostaglandin and carrageenan, when compared to the control group. The redox balance (TAC and MDA) revealed that only EEBWa.v (100 mg/kg) had higher antioxidant potential than the untreated group and the dexamethasone group, p<0.005 and p<0.001, respectively. FAWa.v (100 mg/kg) did not show antioxidant activity superior to EEBWa.v. It was also detected that EEBWa.v and FAWa.v (100 mg/kg) failed to inhibit lipid peroxidation and present a possible antinociceptive mechanism of action by opioid receptors and K+ATP channels. The W. viscosissima stimulates pain control, which can be mediated by both central and peripheral action. The EEBWa.v e FAWa.v showed promising and bioactive effect is statistically similar to morphine, indomethacin and dexamethasone, standard drugs on the market, but with the advantage of antioxidant activity.